Răspuns :
a) x²+7x+6= 6=6*1
x²+6x+x+6= (dam factor comun pe x) 7x=6x+x
x(x+6)+(x+6)=(dam factor comun pe( x+6))
(x+6)(x+1)
b) x²-5x+6 = 6=3*2
x²-3x -2x+6= 5x=-3x-2x
x(x-3)+2(x-3)=
(x+2)(x-3)
c) x²+2x-3 = 3=3*1
x²+3x-x-3 = 2x=3x-x
x(x+3)+(x+3)=
(x+1)(x+3)
la d)nu imi da rezultatul ..
e)x³+x²-16x-16=x²(x-1)-16(x-1)
=(x²-16)(x-1) sper ca te-am ajutat
x²+6x+x+6= (dam factor comun pe x) 7x=6x+x
x(x+6)+(x+6)=(dam factor comun pe( x+6))
(x+6)(x+1)
b) x²-5x+6 = 6=3*2
x²-3x -2x+6= 5x=-3x-2x
x(x-3)+2(x-3)=
(x+2)(x-3)
c) x²+2x-3 = 3=3*1
x²+3x-x-3 = 2x=3x-x
x(x+3)+(x+3)=
(x+1)(x+3)
la d)nu imi da rezultatul ..
e)x³+x²-16x-16=x²(x-1)-16(x-1)
=(x²-16)(x-1) sper ca te-am ajutat